(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2019)
This text tries to tell readers that when there is already a sense that guides the life of a researcher, communicator or educator, the options he takes in his field respond to what he already brings, without needing to make it explicit. The life trajectories of a person visibilize that which gives and that does not give sense to the actions of a person. Hence, turning them into a focus of study for themselves, is of interest, and helps to seek coherence between their discourse and their action. Based on the experience of building a training model, the author proposes readers to convert their own professional journeys into the focus of study and share them, explores the model concept, reviews the authors adventures in the construction of the training model in Spiral 3D + (Facts, moments and stretches) to extract learnings, and reflections in the way and relates the idea of Spiral with our roots.